2017
DOI: 10.1155/2017/8095825
|View full text |Cite
|
Sign up to set email alerts
|

Febuxostat Modulates MAPK/NF‐κBp65/TNF‐α Signaling in Cardiac Ischemia‐Reperfusion Injury

Abstract: Xanthine oxidase and xanthine dehydrogenase have been implicated in producing myocardial damage following reperfusion of an occluded coronary artery. We investigated and compared the effect of febuxostat and allopurinol in an experimental model of ischemia-reperfusion (IR) injury with a focus on the signaling pathways involved. Male Wistar rats were orally administered vehicle (CMC) once daily (sham and IR + control), febuxostat (10 mg/kg/day; FEB10 + IR), or allopurinol (100 mg/kg/day; ALL100 + IR) for 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…Moreover, the present study showed that febuxostat decreases caspase-3 serum level compared to doxorubicin-treated rats. This results in agreement with the research that showed febuxostat reduced the apoptotic marker, namely caspase-3 compared to doxorubicin-treated rats due to the antiapoptotic effect of febuxostat [25].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the present study showed that febuxostat decreases caspase-3 serum level compared to doxorubicin-treated rats. This results in agreement with the research that showed febuxostat reduced the apoptotic marker, namely caspase-3 compared to doxorubicin-treated rats due to the antiapoptotic effect of febuxostat [25].…”
Section: Discussionsupporting
confidence: 93%
“…Pharmacological inhibition of JNK by various synthetic inhibitors, such as AS601245, SP600125, and SR-3306 (Table 1 ), reduces the size of myocardial infarction and attenuates cardiomyocyte apoptosis after ischemia/reperfusion injury (Yue et al, 2000 ; Ferrandi et al, 2004 ; Duplain, 2006 ; Liu et al, 2007 ; Milano et al, 2007 ; Liu et al, 2008 ; Song et al, 2008 ; Shi et al, 2009 , Zhang J. et al, 2009 ; Xu et al, 2011 ; Chambers et al, 2013 ; Khan et al, 2017 ). Introduction of SP600125 into the solution for perfusion of the isolated mouse heart prior to ischemia/reperfusion increases the resistance to opening the mitochondrial permeability transition pore and protects the myocardium against contractile dysfunction and necrosis during ischemia/reperfusion (Zaha et al, 2016 ).…”
Section: Effects Of Modulation Of Jnk Activitymentioning
confidence: 99%
“…Febuxostat and allopurinol (xanthine oxidase inhibitors) pretreatment exerts cardioprotective effects in rats subjected to one-stage left anterior descending coronary artery ligation for 45 min followed by a 60-min reperfusion. Suppression of the active JNK and p38 proteins with the rise in ERK1/ERK2 is more prominent after pretreatment with febuxostat in comparison with allopurinol pretreatment (Khan et al, 2017 ).…”
Section: Effects Of Modulation Of Jnk Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor‐κB is a ubiquitous inducible transcription factor that is responsible for mediating the expression of a large number of genes involved in proliferation, differentiation, inflammation, and tissue injury and repair . NF‐κB is inactive and resides the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%